Mothers’ Knowledge on Neonatal Jaundice attending a Neonatal Intensive Care Unit of a Tertiary Care Hospital in Dhaka, Bangladesh - Afroze, Sharmin; Parvin, Ruma; Sudha, Rabeya Chaklader; Abiduzzaman, MF; Kabir, ANM Ehtesham (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Neonatal jaundice is one of the commonest conditions which require hospital admission in newborns. Objective:To assess the baseline knowledge and attitude of mothers about jaundice in newborn who attended Neonatal Intensive Care Unit (NICU) of a tertiary care hospital. Methods:This descriptive, cross-sectional study was conducted on 324 mothers who attended the Neonatal Intensive Care Unit (NICU)of Dr. M R Khan Shishu (Children) Hospital, Dhaka, Bangladesh, with their sick neonates. A face-to-face interview was done based on a pre-designed structured questionnaire. Results:Mean age of the respondents was 26.17±4.93 years. Most of them (76%) have heard about neonatal jaundice before the survey. Forty two percent mothers thought that it is a mild condition and does not require treatment (45%). Sunlight is the known treatment by most of mothers (65%). Conclusion: There is a serious knowledge gap among mothers regarding the perception, severity and treatment of neonatal jaundice. Education program is needed for pregnant women to increase awareness on this important neonatal issue. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 304-308